Regulations Pertaining to Non-native Fish in Florida Aquaculture - Jeffrey E. Hill (EDIS)
Non-native species comprise the bulk of aquaculture in Florida. It is important for producers to stay informed about current regulations relating to non-native species. FA121, a 6-page fact sheet by Jeffrey E. Hill, describes the regulations concerning the possession, sale and transportation of non-native fish, and the regulatory agencies. Includes references and an appendix with contact information. Published by the UF Department of Fisheries and Aquatic Sciences, August 2006.